Distribusi Konsumsi untuk Cabor Aquatik pada PON Aceh-Sumut 2024: Strategi Implementasi dalam Pengabdian Masyarakat - Regtor Oliver; Octaviananda Siregar; Nico Febrian Gurning; Prama Uda Tarigan; Pras Dio Nanda (Joska: Jurnal Isori Kampar, 2025)
Objectives: The National Sports Week (PON) Aceh-North Sumatra 2024 marked a significant milestone in Indonesian sports history, particularly for aquatic sports that required specialized nutritional management. This community service program focused on developing and implementing consumption distribution strategies for aquatic sports athletes during the event. The program addressed the critical need for proper nutritional support systems that could enhance athlete performance while serving as a model for community-based sports nutrition programs. Methods: Through collaborative partnerships with local communities, sports organizations, and nutritional experts, this initiative established sustainable distribution networks that supported 450 aquatic sports athletes across six competition venues. The methodology employed participatory action research combined with systematic distribution mapping and community engagement protocols. Results demonstrated a 35% improvement in nutritional compliance among athletes, establishment of 12 community-based distribution points, and capacity building for 120 local volunteers in sports nutrition management. Results: The program successfully created a replicable model that integrated community resources with professional sports requirements, generating both immediate performance benefits and long-term community empowerment outcomes. Key findings indicate that community-driven distribution systems can effectively support large-scale sporting events while building local capacity in sports science applications. Conclusion: This initiative provides valuable insights for future sports event management and community-based nutrition intervention programs in Indonesia.